2022
DOI: 10.1111/jipb.13208
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin‐remodeling complexes: Conserved and plant‐specific subunits in Arabidopsis

Abstract: Adenosine triphosphate-dependent chromatin remodeling complexes are important for the regulation of transcription, DNA replication, and genome stability in eukaryotes. Although genetic studies have illustrated various biological functions of core and accessory subunits of chromatin-remodeling complexes in plants, the identification and characterization of chromatin-remodeling complexes in plants is lagging behind that in yeast and animals. Recent studies determined whether and how the Arabidopsis SWI/SNF, ISWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 193 publications
(319 reference statements)
0
34
0
Order By: Relevance
“…Plants conserve multiple SWI/SNF subunits and their misregulation can cause strong developmental defects and altered responses to the environment ( 36 , 37 ). The model plant Arabidopsis presents multiple paralogs of these subunits e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants conserve multiple SWI/SNF subunits and their misregulation can cause strong developmental defects and altered responses to the environment ( 36 , 37 ). The model plant Arabidopsis presents multiple paralogs of these subunits e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The model plant Arabidopsis presents multiple paralogs of these subunits e.g. four ATPases (BRAHMA (BRM), SPLAYED (SYD), MINUSCULE1 (MINU1) and MINU2), four SWI3s (A, B, C, and D) and two SWP73s (A and B), which suggest the formation of multiple variants of the SWI/SNF complex ( 36 ). Through a comprehensive evolutionary study of the conservation of SWI/SNF subunits across eukaryotes, we recently reported a model for the evolution of SWI/SNF subclasses that predicts the presence of two major subclasses in plants ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…The model plant Arabidopsis presents multiple paralogs of these subunits e.g. four ATPases (BRAHMA 3 (BRM), SPLAYED (SYD), MINUSCULE1 (MINU1), and MINU2), four SWI3s (A, B, C, and D), and two SWP73s (A and B), which suggest the formation of multiple variants of the SWI/SNF complex (36). Through a comprehensive evolutionary study of the conservation of SWI/SNF subunits across eukaryotes, we recently reported a model for the evolution of SWI/SNF subclasses that predicts the presence of two major subclasses in plants (35).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin remodeling complexes regulate gene transcription by stabilizing or removing nucleosomes occupying the binding sites for transcription factors [ 95 , 96 ]. The SWI/SNF (switch/sucrose non-fermenting) complex is a well-characterized chromatin-remodeling complex in plants.…”
Section: Chromatin Modifications For Drought-responsive Gene Transcri...mentioning
confidence: 99%